Multiple citizenship and steteless persons - Mudrinić Ljiljana (Megatrend Revija, 2022)
Citizenship is important for every individual, and therefore it is necessary for states to see the right to Citizenship more through the interest of man than the policy they pursue, since beings should enjoy human rights and fundamental freedoms without discrimination, and the corpus of those right and freedom also constitutes the right to citizenship. The paper discusses the international Conventions on Citizenship, especially those that address the vulnerable, stateless persons and refugees, and are dedicated to solving the problem of their status and their right to citizenship. The right to multiple citizenship, as well as the citizenship of the European Union and the member states, occupies an important place in the work.